Aeroacoustic Simulations Using Compressible Lattice Boltzmann Method (Advances in Applied Mathematics and Mechanics, 2018)
This paper presents a lattice Boltzmann (LB) method based study aimedat numerical simulation of aeroacoustic phenomenon in flows around a symmetricobstacle. To simulate the compressible flow accurately, a potential energy double-distribution-function(DDF) lattice Boltzmann method is used over the entire computationaldomain from the near to far fields. The buffer zone and absorbing boundarycondition is employed to eliminate the non-physical reflecting. Through the direct numericalsimulation, the flow around a circular cylinder at $Re$=150, $M$=0.2 and theflow around a NACA0012 airfoil at $Re$=10000, $M$=0.8, $α$=$0^◦$ are investigated. Thegeneration and propagation of the sound produced by the vortex shedding are reappearedclearly. The obtained results increase our understanding of the characteristicfeatures of the aeroacoustic sound.